IMAGINED SPACES AND MEMORY IN WALCOTT’S POETRY - Olasode, Chikodi Adeola (UC Journal: ELT, Linguistics and Literature Journal, 2025)
The poetry of Derek Walcott is deeply rooted and attached to the landscapes of his land, and he infuses his poetry with memories from the Caribbean. He employs imagery in his poems that makes real and imaginary a sense of place, which is influenced by St. Lucia, where he grew up, and collective colonial history. This study examines the significance of imagined spaces and memory in Derek Walcott's poetry, exploring how the poet uses mental images and visions to create landscapes, settings, and atmospheres that delve into complex ideas, emotions, and thoughts. Imagination as well as memory plays a huge role in his poems, and it is infused throughout his works. This perfectly encapsulates the pieces of works of Walcott where poetry serves as a fusion of the real world with one’s visions. This study employs a variety of theoretical lenses, among them postcolonial theory, cultural studies, and ecocriticism, to explore the consequences of Walcott's poetry for our conception of identity, location, and remembrance. Walcott's poetry is a strong medium through which one can explore the intricacies of humanity, and this research proves the need for his work in not only literary studies but also cultural studies and others.